2021
DOI: 10.1186/s13063-021-05394-3
|View full text |Cite
|
Sign up to set email alerts
|

Acupuncture for combat post-traumatic stress disorder: trial development and methodological approach for a randomized controlled clinical trial

Abstract: Background Post-traumatic stress disorder (PTSD) is a significant public health problem, affecting approximately 7% of the general population and 13–18% of the combat Veteran population. The first study using acupuncture for PTSD in a civilian population showed large pre- to post-treatment effects for an empirically developed verum protocol, which was equivalent to group cognitive behavior therapy and superior to a wait-list control. The primary objective of this study is to determine both clin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 55 publications
0
6
0
Order By: Relevance
“…A total of 56 studies were included, with 19 clinical studies and 37 animal studies. Two studies (Prisco et al, 2013 ; King Heather et al, 2015 ) used ear acupuncture, one study (Wu et al, 2013 ) used scalp acupuncture, one study (Yang et al, 2022 ) used CO 2 laser stimulation, one study (Feng et al, 2019 ) used TEAS, and other studies (Fang et al, 2012 ; Li, 2012 , 2014 , 2018 , 2020 ; Wang et al, 2012 , 2015 ; Hou et al, 2013a , b , 2021 ; Wang, 2013 , 2019 ; Engel et al, 2014 ; Li and Zhao, 2014 ; Zhao et al, 2014 , 2019 , 2020 ; Xie et al, 2015 ; Zheng, 2015 ; Zheng et al, 2015 ; Zhou et al, 2015 , 2019 ; Lu et al, 2016 ; Zhu et al, 2016 , 2022 ; Han, 2017 ; Li et al, 2017 , 2020a , b ; Ding, 2018 ; Oh et al, 2018 ; Zhao Y. et al, 2018 ; Zhao Z. et al, 2018 ; Chen et al, 2019 , 2020 , 2021 ; Liu et al, 2019 , 2020 ; Moiraghi et al, 2019 ; Wei et al, 2019 ; Xue et al, 2019 ; Yu et al, 2019 ; Zhang et al, 2019 ; Zhu and Lu, 2019 ; Alvear, 2021 ; Hollifield et al, 2021 ; Abanes et al, 2022 ; Lee and Pan, 2022 ; Song et al, 2022 ; Sun Y. et al, 2022 ; Zhou C. et al, 2022 ) used filiform needle (detail in…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A total of 56 studies were included, with 19 clinical studies and 37 animal studies. Two studies (Prisco et al, 2013 ; King Heather et al, 2015 ) used ear acupuncture, one study (Wu et al, 2013 ) used scalp acupuncture, one study (Yang et al, 2022 ) used CO 2 laser stimulation, one study (Feng et al, 2019 ) used TEAS, and other studies (Fang et al, 2012 ; Li, 2012 , 2014 , 2018 , 2020 ; Wang et al, 2012 , 2015 ; Hou et al, 2013a , b , 2021 ; Wang, 2013 , 2019 ; Engel et al, 2014 ; Li and Zhao, 2014 ; Zhao et al, 2014 , 2019 , 2020 ; Xie et al, 2015 ; Zheng, 2015 ; Zheng et al, 2015 ; Zhou et al, 2015 , 2019 ; Lu et al, 2016 ; Zhu et al, 2016 , 2022 ; Han, 2017 ; Li et al, 2017 , 2020a , b ; Ding, 2018 ; Oh et al, 2018 ; Zhao Y. et al, 2018 ; Zhao Z. et al, 2018 ; Chen et al, 2019 , 2020 , 2021 ; Liu et al, 2019 , 2020 ; Moiraghi et al, 2019 ; Wei et al, 2019 ; Xue et al, 2019 ; Yu et al, 2019 ; Zhang et al, 2019 ; Zhu and Lu, 2019 ; Alvear, 2021 ; Hollifield et al, 2021 ; Abanes et al, 2022 ; Lee and Pan, 2022 ; Song et al, 2022 ; Sun Y. et al, 2022 ; Zhou C. et al, 2022 ) used filiform needle (detail in…”
Section: Resultsmentioning
confidence: 99%
“…With the increasing availability of acupuncture worldwide, patients with PTSD are increasingly seeking and accepting acupuncture. Many studies have confirmed the effectiveness of acupuncture for PTSD (Yang and Zhang, 2012;Zhang, 2013;Jin et al, 2014Jin et al, , 2015Zheng et al, 2014;Zhao et al, 2015;Han et al, 2016Han et al, , 2017Grant et al, 2018;Ding et al, 2020;Song et al, 2020Song et al, , 2021Hollifield et al, 2021;Kwon et al, 2021;Li et al, 2021). Because the number of studies in the last 10 years accounts for the vast majority and is limited by research technology, there are some differences in outcomes between the long-term research and the current research, so we searched various databases from 1 January 2012 to 27 November 2022.…”
Section: Discussionmentioning
confidence: 97%
“…No extant data were available for sample size or power estimates on secondary hypotheses. A description of study methods has been published . Written informed consent was obtained.…”
Section: Methodsmentioning
confidence: 99%
“…Each of 20 items is rated from 0 (absent) to 4 (severe) and summed into a single severity score. More complete CAPS-5 scoring rules applied in this study have been published …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation